Letter from Ellen Leahy to Patrick McCartan regarding the payment of "Mr. Doyle", Larry De Lacy's legal representative, and an account of a meeting with a "Mrs. Denis Buckley" and her daughter from Macroom, County Cork, - Leahy, Ellen Mary Agnes, 1865- (1920)
Letter describes how Mrs. Buckley views on Sinn Féin. Ellen Leahy has suspicions that Mrs. Buckley is cooperating with her brother in Oregon in "some kind of slave-trade".